2018
DOI: 10.1590/1678-457x.00217
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest evaluation of tomato genotypes with dual purpose

Abstract: (Dnline) vitamins A, B1, B2, B5 and C, fibers and minerals, besides its low caloric power (Alvarenga & Coelho, 2013). High quality fruit production depends on environmental factors such as light and weather, besides farming practices, and genetic variability among the materials is a strategy for crop improvement (Causse et al., 2003). Horticultural products quality is associated with its integrity, flavor and texture, interrelated to other physical, chemical and nutritional properties (Chitarra & Chitarra, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…Tomato fruits usually have a pH below 4.6, and, this way, they are considered acidic foods (Anthon & Barrett 2012). Although the citric acid concentration indicated fruits with a low acidity, in the present study, the fruits presented pH values below 4.6, agreeing with the results for tomato fruits found in the literature (Figàs et al 2015, Gatta et al 2015, Peixoto et al 2018.…”
Section: Nº Of Bunchessupporting
confidence: 91%
“…Tomato fruits usually have a pH below 4.6, and, this way, they are considered acidic foods (Anthon & Barrett 2012). Although the citric acid concentration indicated fruits with a low acidity, in the present study, the fruits presented pH values below 4.6, agreeing with the results for tomato fruits found in the literature (Figàs et al 2015, Gatta et al 2015, Peixoto et al 2018.…”
Section: Nº Of Bunchessupporting
confidence: 91%
“…The average fruit mass may be influenced by environmental factors, genotypes, number of stems per plant, number of fruits per plant, planting density and number of seeds per fruit (Peil et al, 2014;Peixoto et al, 2018). In the present study, an inverse relationship between the number of fruits per plant and the average fruit mass was confirmed.…”
Section: Resultssupporting
confidence: 72%
“…It means that for consumers who like milder tomatoes, yellow fruit is recommended. The levels of vitamin C and total acidity are in agreement with research data reported in scientific literature (Peihoto et al, 2018, Pinela et al, 2016), but less than others (Asensio et al, 2019, Vinha et al, 2013. Taste index is parameter, which characterizes the quality and taste of tomatoes.…”
Section: Resultssupporting
confidence: 88%